Analysis of health professionals’ susceptibility to immuno-preventable diseases: from vaccine status - Pinto, Agnes Caroline Souza; Almeida, Maria Irismar de; Pinheiro, Patrícia Neyva da Costa (Rev Rene, 2011)
The existent biological risks in primary health care centers need to be evaluated. So we aimed to describe the vaccination status of graduate professionals that work in the Family Health Program of Morada Nova-CE, seeking to verify their susceptibility to immunopreventable diseases. This is a descriptive exploratory study carried out from April to December 2008. A questionnaire was used for the data collection on demographic situation and immune-preventable diseases and vaccination history. 47 professionals were evaluated: 48% hadn’t been vaccinated for the main diseases, 26% didn’t have a vaccination card, and only 5% had their children’s vaccination card; the biggest coverage was for BCG with 81%, followed by 64% for Hepatitis B with only 6.6% with serological proof; and 60% had antitetanic vaccination. The results show these professionals’ vulnerability, making necessary the creation of an immunization program for those who work in primary health care, articulating interventions that may reduce the exposure to biological risks in the work environment.